Overview of: "Valuing Developmental Crime Prevention". Issue 2 (May 2013) - Manning, Matthew; Smith, Christine; Homel, Ross
<x xml:space="preserve">Abstract</x> Research Summary Developmental crime prevention programs produce positive returns on investment. Previous studies of such returns have not adequately quantified and weighted impacts across multiple domains of quality of life (e.g., social‐emotional development and family well‐being) or have provided a protocol for deciding between programs that recognizes these multiple domains (i.e., propose a method for the ranking of program alternatives). We adapted a multiple‐criteria decision‐making (MCDM) technique to address these deficiencies. Incorporating subjective decisions (a survey of those individuals who directly affect policy decisions) and objective evidence (the effect sizes from a meta‐analysis of longitudinal intervention outcomes) allowed us to construct a common metric for making structured choices between diverse developmental crime prevention program options. Our results show that a structured preschool program that incorporates family intervention and support was the most preferred option to reduce youth crime. Policy Implications The adapted MCDM technique employed in this study can be used to evaluate many crime prevention policy options that have effects that are spread across multiple domains and for which objective evidence from past research can usefully be combined with stakeholder judgments to recommend a preferred option.